Hadist Tematik Komunikasi Pembangunan: Konsep “Masjid” dan “Kerja” - Andi Kardian Riva'i (JURNAL SOSIO-KOMUNIKA, 2022)
This study focuses on the purpose of describing the meaning of religious symbols in the concept of development communication, especially with an Islamic perspective approach which is interpreted as a symbol that is cult and sacred by society, especially Islam. The compilation method is based on library research and the software program Encyclopedia Hadith 9 Imam accesses nine books of primary sources of hadith to facilitate the completion of the critical method of sanad and subject of this study. There are two substances in the discussion that was built, namely: first, "mosque" as a symbol of the development of Islamic society. The paradigm and understanding of the mosque being only used as a place of prostration is a narrow understanding, even though the mosque is very strategic in the development of Muslims, because in addition to being used for worship, it can also be used for activities with social, political, legal, economic or other nuances. other socio-cultural activities. The mosque is essentially not only a place of prostration that reduces the role of the mosque to just a place of worship and a symbol of religiosity, but more than that, people use mosques as a means to initiate strategies, build and maintain civil civilization. Second, "Work" as a development effort and is one of the concepts of concern in Islam. Work is basically a fundamental reality for humans, therefore it is the essence of nature that is always carried along at every level of human development, because work is a mirror of the implementation of religious orders and at the same time carrying out community economic development.